The Barbie movie and the psychological experience of gender inequality - Nolan, Eden, E., author (Colorado State University. Libraries, 2024)
As societies reach toward gender equality, it is often assumed that issues of gender inequality and discrimination are rare. However, instances of gender discrimination and inequality have become more subtle than overt, and still cause harm across individuals. The transition of gender discrimination from overt instances to subtle instances has caused society to be dismissive of statements that claim gender inequality is still a significant issue today. In this work, the 2023 Barbie movie is evaluated as a statement of gender inequality in the United States. The purpose of this paper is to evaluate how subtle gender inequality manifests itself, and to explain this manifestation through the psychological explanations of gender inequality. The thesis addresses questions such as, "How is gender discrimination seen today?", "How does gender discrimination impact people?", and "Why does gender discrimination still exist today?" through the analysis of the Barbie movie. The purpose of the thesis is to highlight examples of gender discrimination, and thoroughly analyze a piece of media that acknowledges gender inequality, and address that gender inequality is a problem that is continuously experienced across cultures. The movie is separated by scenes, where each scene is explained and evaluated through psychological studies that explain the specific experience of the related scene. The investigation of gender inequalities represented in the Barbie movie culminates in an artistic reflection that elaborates on the author’s experience with gender.
HONR 499: Honors Thesis.
Keywords: Barbie (2023); gender inequality; gender discrimination; art